2022
DOI: 10.1093/pcp/pcac012
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Low UV-B Dose Induces DNA Double-Strand Breaks Mediated Onset of Endoreduplication in Vigna radiata (L.) R. Wilczek Seedlings

Abstract: Multiple lines of evidence indicate that solar UV-B light acts as an important environmental signal in plants, regulating various cellular and metabolic activities, gene expression, growth, and development. Here, we show that low levels of UV-B (4.0 kJ m-2) significantly influences plant response during early seedling development in the tropical legume crop Vigna radiata (L.) R. Wilczek. Exposure to low doses of UV-B showed relatively less growth inhibition, yet remarkably enhanced lateral root formation in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…It is already evident that Mel can induce lateral roots in plants with different effective concentrations(Ren et al, 2019) through ROS signalling, where H 2 O 2 serves as a signalling molecule to activate down-stream ROS/Ca 2+ signalling pathway(Chen et al, 2019;Bian et al, 2021). In this study, we have shown the connecting link between ROS-induced DNA-damage, endoreduplication and lateral root formation De et al, (2022). reported that the treatment of Vigna radiate with a low dose (4.0 kJ m −2 ) of UV-B is coupled with a retarded primary root growth and an increased number of lateral roots, whereas, reduced primary root growth and lateral root numbers had been observed in high dose (8.0 kJ m −2 ) group.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…It is already evident that Mel can induce lateral roots in plants with different effective concentrations(Ren et al, 2019) through ROS signalling, where H 2 O 2 serves as a signalling molecule to activate down-stream ROS/Ca 2+ signalling pathway(Chen et al, 2019;Bian et al, 2021). In this study, we have shown the connecting link between ROS-induced DNA-damage, endoreduplication and lateral root formation De et al, (2022). reported that the treatment of Vigna radiate with a low dose (4.0 kJ m −2 ) of UV-B is coupled with a retarded primary root growth and an increased number of lateral roots, whereas, reduced primary root growth and lateral root numbers had been observed in high dose (8.0 kJ m −2 ) group.…”
supporting
confidence: 51%
“…Regarding lateral root formation, Davis et al, (2016) reported the inhibition of lateral roots in Arabidopsis by DNA-damage causing the up-regulation of cytokinin biosynthesis genes. Conversely, De et al, (2022) showed an enhanced level of lateral root formation in Vigna radiata after exposure to the low dose of UV-B for a longer period. Two possibilities may come out from these studies: firstly, lateral root development under DNA-damage stress varies with plant species, and secondly, it is the extent of DNA-damage that decides whether lateral root will develop or not.…”
Section: Introductionmentioning
confidence: 88%
“…For instance, the mammalian genome encodes nearly 20 CDKs, whereas in yeast there are only six [ 6 ]. Despite its role in cell cycle progression, CDKs are also involved in DNA repair, transcriptional regulation, and proteolytic degradation mechanisms in mammals [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to UV radiation is unavoidable for plants when capturing sunlight for photosynthesis. UV affects many development processes in plants, such as endoreduplication, hypocotyl and cotyledon development, flavonoid accumulation, and DNA stability (De et al, 2022; Li et al, 2013; Ries et al, 2000; Shi and Liu, 2021; Verdaguer et al, 2017). In addition, UV influences plant development by inducing reactive oxygen species (ROS) and antioxidants (Gill et al, 2015; Sinha and Häder, 2002).…”
Section: Introductionmentioning
confidence: 99%